A SYSTEMATIC LITERATURE REVIEW OF FACTORS INFLUENCING PURCHASE INTENTION ON SOCIAL ENTERPRISE PRODUCTS - Zhen-Yee Tan; Jeffrey Cheah (Journal of Islamic, Social, Economics and Development, 2022)
Social enterprise is a hybrid entity that applies a business model to achieve financialvalue while pursuing a social or environmental agenda. However, the development of a socialenterprise in many developing countries like Malaysia is still not mature, where most of themface a survival crisis due to financial difficulties. Social entrepreneurs need to comprehend thefactors that might affect the purchase intention of their customers. Thus, this study establisheda systematic review, content analysis, and gap analysis method to identify and conceptuallyframing the most prevalence variable that determines the customer purchase intentions. First,20 core articles were selected from 1,576 articles that published in indexed journals. Next, anin-depth content analysis was established to reveal the most prevalence variables that chosenand examined in the past empirical research. Hereafter, this study validated each variablebased on the commonly used theory, namely the Theory of Planned Behaviour, in explainingand predicting the decision-making process of product purchasing. Subsequently, a gapanalysis was established to explore important empirical findings in the previous studies anddetermine the contradictory evidence and knowledge gaps. The research findings could be apractical guide for social entrepreneurs in constructing their marketing strategies to increasetheir revenue. Consequently, by improving the social enterprise's performance, it will helpaddress social and environmental issues. Future studies might extend this study by empiricallyexamine the model in a different context.